ChemInform Abstract: A Combined Transition‐Metal‐Catalyzed and Photopromoted Process: Synthesis of 2, 3‐Fused 4‐Phenylnaphthalen‐1‐yl Carboxylates from 1, 7‐Diaryl‐1, 6‐diynes. Issue 44 (15th October 2015) - Yamamoto, Yoshihiko; Mori, Shota; Shibuya, Masatoshi
Abstract The Ru‐catalyzed hydrocarboxylative cyclization of 1, 7‐diphenyl‐1, 6‐diynes (I) with AcOH gives rise to dienes (III), which are converted into 2, 3‐fused 4‐phenylnaphthalen‐1‐yl carboxylates (IV) by oxidative photocyclization.